PENGARUH KUALITAS LAYANAN DAN PEMULIHAN LAYANAN TERHADAP LOYALITAS DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi Pada Nasabah Bank Mandiri di Surabaya) - RUSPIANTONO PUTRA, HELMI; LESTARI ANDJARWATI, ANIK (Jurnal Ilmu Manajemen (JIM), 2018)
Analyze in study efect of service quallity and service recover on loyalty in mediated variable. Technique sampling is non probability with 220 sample respondents. The measuring instrument used is a questionnaire. The measurement scale in this study uses a Likert scale. Analysis tools use path analysis with the AMOS 22 program. The results showed that the relationship between service quality and service recovery variables had a positive and significant effect on loyalty and satisfaction so that mediation was partially proven. Service quality has a positive effect on satisfaction, service recovery has a positive effect on satisfaction, satisfaction has a positive effect on loyalty, service quality has a positive effect on loyalty, and service recovery has a positive effect on loyalty.